Correlation between clinical severity and chest X-ray grade using the Brixia score in pneumonia patients confirmed with the Delta variant of Covid-19 - Kantilaras, Anggita Putri; Pamungkas, Rifqy Hendrian (Institute of Computer Science (IOCS), 2025)
Background: COVID-19 is a disease that attacks the respiratory organs. This disease can be transmitted directly or indirectly through droplets released by an infected individual. The clinical manifestations that appear vary depending on the degree of severity. Chest X-ray is one of the supporting examinations to establish a diagnosis of COVID-19. There are several chest X-ray assessments used to determine the severity of pneumonia in individuals infected with COVID-19, one of them is Brixia Score. The aim of this study is to determine the correlation between the degree of clinical severity and the degree of chest X-ray using Brixia Score in pneumonia patients confirmed with delta variant of COVID-19. Method: This study is an observational study using a correlative analysis method with a cross-sectional research design. Sampling in this study was carried out by non-random consecutive sampling from medical record data at the RSUD Merah Putih Magelang, totaling 38 samples. The statistical analysis used is the Spearman's test. Result: In this study, the correlation coefficient value was 0.851 and p < 0.05, which states that there is a strong correlation between the degree of clinical severity and the degree of chest X-ray using Brixia Score. Conclusion: There is a strong correlation between the degree of clinical severity and the degree of chest X-ray using the Brixia Score in pneumonia patients confirmed with delta variant of COVID-19.